KEBUTUHAN TENAGA PELAPORAN DENGAN METODE ANALISIS BEBAN KERJA PADA MASA PANDEMI COVID-19 DI RSU “X” - Widia Nurrul Irsani; Sali Setiatin; Aris Susanto (Politeknik Negeri Jember, 2022)
Reporting personnel are one of the important human resources to determine the performance of the medical record work unit. Determining the right number of human resources must be based on systematic calculations, one method that can be used is the workload analysis method. The Covid-19 pandemic period requires health service facilities including hospitals to report related to Covid-19 events, which has increased the workload of medical recorders in the reporting section. At the General Hospital